Dynamics of cardiovascular system and adaptive potential in students with chronic bronchitis - Петрухнов, Олександр (Slobozhanskyi Herald of Science and Sport, 2018)
Oleksandr Petruhnov Purpose: to determine the impact of the physical rehabilitation program on the state of the cardiovascular system and changes in the adaptive capacity of students with chronic bronchitis. Material & Methods: theoretical analysis of literature and generalization of scientific, methodological and specialized literature; pulseometry, arterial tonometry, a technique for determining the adaptive potential by R. M. Baevsky; methods of mathematical statistics. Results: a comprehensive program of physical rehabilitation was made taking into account the two stages of the period of convalescence, clinical and biological recovery, for students of the same group, additional application of varieties of walking and running on various health-normalizing regimes. After applying the program of physical rehabilitation of students of both groups, a slowdown in the recovery of all cardiovascular parameters and changes in the adaptive potential of the circulatory system was noted, however, the best results were obtained in a group of students, additionally, the versions of walking were used in various health-normalizing regimes with a combination of permutations of hand movements. Сonclusion: confirmation of the effectiveness of the developed program of physical rehabilitation was a statistically significant improvement in the cardiovascular system, a slowdown in recovery processes after exercise, an increase in the number of students with a state of satisfactory adaptation.